1054. A Randomized Controlled Trial of Hepatitis B virus (HBV) Revaccination among Men Who Have Sex with Men and Were Born in the Era of Universal Neonatal HBV Immunization. (31st December 2020) - Huang, Yi-Chia; Sun, Hsin-Yun; Chuang, Yu-Chung; Huang, Sung-Hsi; Liu, Wen-Chun; Su, Yi-Ching; Chang, Sui-Yuan; Hung, Chien-Ching
Abstract: Background: People who have lost anti-HBs antibody decades after neonatal vaccination but are at high risk of acquiring HBV are recommended to undergo HBV revaccination. The optimal revaccination strategy remains unknown, however. We aimed to compare the efficacy of revaccination with standard- (20-μg) vs double-dose (40-μg) of HBV vaccine among men who have sex with men (MSM). Methods: MSM aged ≥ 20 years who had undergone HBV vaccination at birth and tested negative for HBsAg and anti-HBc with anti-HBs titer < 10 mIU/ml were randomized to receive standard- or double-dose HBV vaccine (1:1 ratio with a block size of 4) at weeks 0, 4, and 24. Plasma HIV RNA < 50 copies/ml for ≥ 6 months was required for HIV-positive MSM. The primary endpoint was the proportion of participants achieving anti-HBs ≥ 10 mIU/ml at week 28. The secondary endpoints were high-titer response (≥ 100 mIU/ml) at weeks 28 and 48, serological response at week 48, and adverse events (AE). Results: From Sep 2017 to Jun 2020, 161 HIV-positive and 77 HIV-negative MSM were enrolled. The serological response at week 28 was 86.2% for the standard-dose group and 94.9% for the double-dose group (p=0.070). The proportion of high-titer response was higher for the double-dose group than the standard-dose group at 28 weeks (84.6% vs 70.1%, p=0.041). The respective serological response and high-titer response at week 48 were 81.3% and 58.7% for the standard-dose group vs 94.2% and 78.3% for the double-dose group (p=0.023 and p=0.013, respectively). In generalized estimating equations model, double-dose HBV revaccination (aOR, 1.7; 95% CI, 1.1-2.8) and baseline anti-HBs ≥ 2.5 mIU/ml (aOR, 7.5; 95% CI, 4.3-13.5) were associated with high-titer responses. HIV infection was not associated with serological response (aOR, -1.2; 95%CI, -2.47-1.60) and high-titer response (aOR, -1.1; 95%CI, -1.95-1.49). The double-dose group had a higher rate of local AEs (27.2% vs 38.7%, p=0.118). One (0.8%) severe AE occurred in the double-dose group, which resolved without sequelae. Table 1. Baseline characteristic of participants Table 2. Serological response after revaccination Table 3. GEE model of vaccine efficacy and associated factors Conclusion: Double-dose HBV revaccination results in sustained serological and high-titer responses among MSM who were born in the era of universal neonatal HBV vaccination. Anti-HBs titer ≥ 2.5 mIU/ml at baseline is associated with high-titer response. Disclosures: All Authors : No reported disclosures